Quantitative Determination of Sinensetin in Orthosiphon stamineus Leaves by Thin-Layer Chromatography and Imaging Densitometry: Short Communication (Biological Sciences - PJSIR, 2005)
An analytical method for the determination of sinensetin in Orthosiphon stamineus leaves by a thin-layer chroma- tography-imaging densitometric method was developed. The procedure consisted of extraction of dry leaf powder with 50% methanol and high performance preparative thin layer chromatography (HPTLC). HPTLC was performed on silica gel plate, using chloroform-ethylacetate (60:40) as the developing solvent for sinensetin. The plate was scanned with a reflectance densitometer at 190 nm. The quantification was done by the external standard method.